GLOBALISASIDAN GENEALOGI STABILITAS DOMESTIK: TANTANGAN DAN KEBIJAKAN TERHADAP PENGUNGSI DAN PENCARI SUAKA - Elviandri Elviandri (JOURNAL EQUITABLE, 2017)
Factors that cause Indonesia to be selected as a transit country for refugees and asylum seekers, among them are first, Indonesia has a vast marine territory of long coastline, but is not supported by strict rule of law. Secondly, Indonesia's position is very weak in addressing the problem of asylum seekers and refugees from other countries because it has no national regulations that specifically address the issue. Third, the lack of facilities and infrastructure in handling refugees and asylum seekers. Fourth, the presence of UNHCR in Jakarta became a refugee attraction. Fifth, the culture or culture of Indonesia, known for its hospitality, gives the impression that Indonesians can easily accept the arrival and whereabouts of refugees. The setting up of asylum seekers and refugees should be placed in immigration legislation because the issue of asylum seekers and refugees is a foreigner's (immigration status) problem, which touches on international aspects. The handling of refugees, immigrants and asylum seekers faces several obstacles in the process of handling them: First, Internal Constraints; A) the absence of standard standards in legislation regarding the handling of illegal immigrants. b) The legal vacuum that comprehensively regulates asylum seekers and refugees in Indonesian positive law, weakens coordination among agencies in the field. c) Lack of immigration quarantine facilities to accommodate asylum seekers and refugees, d) Limited regular funds. Second, External Constraints. a) Local Government objected to the additional burden of the arrival of troubled foreigners. b) The often sharp distinction between regional culture and the culture of displaced potential foreigners brings about social conflict. c) Arise of social jealousy of the refugees received free humanitarian assistance in the form of shelter and living expenses, while local residents live in a state of deprivation. Residents do not realize that the aid is not from the government, but from UNHCR and or IOM. D) Often the assimilation between asylum-seeker men and refugees with local women, precisely leaves the child's burden. -the children who turn up when repatriation or resettlement are not brought along.